Development, Characterization and In Vitro Evaluation of Flurbiprofen Solid Dispersions using Polyethylene Glycols as Carrier - Bindu Yadav, Y. S. Tanwar (Journal of Applied Pharmaceutical Science, 2016)
The purpose of the present investigation was to increase the solubility and dissolution rate of flurbiprofen (FLB) by the preparation of its solid dispersion with polyethylene glycol 4000 and 6000 as carriers using solvent evaporation method (SM) and kneading method (KM). Drug polymer interactions were investigated using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), x-ray diffraction (XRD). The prepared solid dispersions were characterized by IR spectroscopy, which suggests no interaction of drug with carriers. XRD and DSC study indicates reduction in drug crystallinity. Drug solubility was more and also the dissolution was rapid for Flurbiprofen solid dispersions compared to pure drug.
Keywords: Solubility, FLB, Solid dispersion, IR spectroscopy, XRD, DSC.